Efficacy and safety of iris-supported phakic lenses (Verisyse) for treating moderately high myopia - Melisa Ahmedbegović Pjano; Amila Alikadić-Husović; Senad Grišević; Adis Pašalić; Ajla Pidro; Mirko Ratković; Maja Bohač; Nikica Gabrić; Refet Gojak (Medicinski glasnik, 2016)
Aim: To evaluate efficacy and safety of iris-supported phakic lenses (Verisyse) for treating moderately high myopia. Methods: This prospective clinical study included 40 eyes from 29 patients, who underwent implantation of Verisyse for correction of myopia from -6.00 to -14.50 diopters (D) in the Eye Clinic ‘’Svjetlost’’, Sarajevo, from January 2011 to January 2014. Uncorrected distance visual acuity (UDVA), manifest residual spherical equivalent (MRSE), postoperative astigmatism, intraocular pressure (IOP), endothelial cell (EC) density were evaluated at one, three, six and twelve months. Corrected visual acuity (CDVA), index of safety and efficacy were evaluated after 12 months. Results: Out of 29 patients 15 were males and 14 females, with mean age of 27.9 ± 5.0. After 12 months 77.5% eyes had UDVA ? 0.5 and 32.5% had UDVA ? 0.8. Mean MRSE was 0.55D ±0.57D and mean postoperative astigmatism -0.86D ± 0.47D. Efficacy index was 1.09 ± 0.19 and safety index 1.18 ± 0.21. One eye (2.5%) lost two Snellen lines and three eyes (7.5%) one line, 11 eyes (27.5%) gained one line, and five eyes (15.5%) gained two lines. EC loss after 12 months was 7.59 ± 3.05%. There was no significant change of IOP after one year follow up. Conclusion: Implantation of iris-supported phakic lenses (Verisyse) for treating moderately high myopia is an efficient and safe procedure.
Keywords: refractive surgery; diopter; refractive intraocular lens